Conjugated Oligo- and Polymers for Bacterial Sensing - Löffler, Susanne; Antypas, Haris; Choong, Ferdinand X.; Nilsson, K. Peter R.; Richter-Dahlfors, Agneta (Frontiers in Chemistry, 2019)
Fast and accurate detection of bacteria and differentiation between pathogenic and commensal colonization are important keys in preventing the emergence and spread of bacterial resistance towards antibiotics. As bacteria undergo major lifestyle changes during colonization, bacterial sensing needs to be achieved on different levels. In this review, we describe how conjugated oligo- and polymers are used to detect bacterial colonization. We summarize how oligothiophene derivatives have been tailor-made for detection of biopolymers produced by a wide range of bacteria upon entering the biofilm lifestyle. We further describe how these findings are translated into diagnostic approaches for biofilm-related infections. Collectively, this provides an overview on how synthetic biorecognition elements can be used to produce fast and easy diagnostic tools and new methods for infection control.